The Communist Party Influence on the Chekists, 1944–1953 - Starkauskas, Juozas (Genocidas ir rezistencija, 2004)
Even as they competed for power, influence, and material goods, the Communist Party functionaries and the Chekists (state security personnel) were closely united by their common purpose of consolidating the occupation regime, the so called Soviet system, and by their aim to consolidate the autocratic power.Until 1947, the independent work of the LKP(b) CC (the Lithuanian Communist (Bolshevik) Central Committee) and its divisions in districts was restricted by the VKP(b) (All-Union Communist (Bolshevik) Party) CC Lithuanian bureau and the agent of the USSR NKVD-NKGB for Lithuania, Ivan Tkachenka. It was actually not the puppets in Vilnius who had the real power, but the power structures of the occupiers, the influence of which remained decisive even after 1947, when the pretence was created that all decisions would be made in Vilnius. After 1947, the LKP(b) CC bureau, especially the First Secretary, Antanas Sniečkus established considerably more control over the Chekists, especially over their personnel, and, to some extent, over their activities. The CC bureau would depose the heads of the MGB district divisions, while the party district committees had authority to expel the division heads of MGB local districts. In order to replace the district division heads, the Central Committee had to be consulted.To maintain relations with the Chekists, a special sector in the CC operated until 1949; later there was an administrative division, headed by A. Moskvinov (until 1950) and V. Bylinski, which had great influence.The Chekists would be replaced and generally criticized mostly for their inability to fight; as well they would be accused of transgressions and even crimes, such as drunkenness, thefts, various other violations. Moreover, the Party committees were required to fight against real enemies; not simply shooting or arresting innocent persons, while the true "bourgeois nationalists" were free. However, they were not in fact able to select the replacements they wished, they did not even know the Chekist personnel, especially those continuously sent from the East. The MVD-MGB would appoint new Chekists at their own discretion.The CC and Party district committees would strictly control the deployment of the Chekist army posts; some district Party committees would also attempt to control their operational plans. Sometimes, they attempted to implement plans together with the Chekists, although most often they obeyed general orders, which were derived from the decisions of the CC bureau.In addition to matters of personnel and other general plans, the Party exerted influence on the Chekists by debriefing oral reports or examining their written reports which had to be submitted to the Party committees by the middle of 1945. If Chekists were seeking or were already ensconced in their positions, the Party organs would write references and recommendations which could determine a career path for the Chekists. In general, the Party committees could control the tactics of the Chekist organs to some extent, while the strategic aims of both, that is, of the Party and the Chekists was the same.
Keywords: communist party; repressive structures; armed resistance; repressions; sovietisation